2017
DOI: 10.1681/asn.2017060599
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Lymphocytes in the Kidney

Abstract: It has become evident that nonlymphoid tissues are populated by distinct subsets of innate and adaptive lymphocytes that are characterized by minimal exchange with recirculating counterparts. Especially at barrier sites, such as the skin, gut, and lung, these tissue-resident lymphocyte populations are ideally positioned to quickly respond to pathogens and other environmental stimuli. The kidney harbors several classes of innate and innate-like lymphocytes that have been described to contribute to this tissue-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 86 publications
0
52
0
2
Order By: Relevance
“…A specific population of interest are tissue-resident NK cells, which can reside in tissue for years and execute local tasks. Studies of tissue-resident NK cells from human livers [ 7 10 ], lungs [ 10 , 11 ], lymph nodes [ 12 , 13 ], uterus [ 14 ], kidneys [ 15 ] and spleens [ 13 , 16 ] have elucidated how tissue-resident NK cells are distinct from NK cells circulating in the peripheral blood, showing crucial differences in phenotypical and functional characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A specific population of interest are tissue-resident NK cells, which can reside in tissue for years and execute local tasks. Studies of tissue-resident NK cells from human livers [ 7 10 ], lungs [ 10 , 11 ], lymph nodes [ 12 , 13 ], uterus [ 14 ], kidneys [ 15 ] and spleens [ 13 , 16 ] have elucidated how tissue-resident NK cells are distinct from NK cells circulating in the peripheral blood, showing crucial differences in phenotypical and functional characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study which demonstrates the profile of ILC subsets in AKI. Previous studies have focused on therapeutic modula-tion of type 2 immunity, via maneuvers to amplify ILC2s, on the outcome of AKI [22]. Huang et al [31] showed that Il-25-treated mice subjected to renal IRI display increased serum levels of IL-4, IL-5, and IL-13 in association with increased frequencies of ILC2s and improved renal function.…”
Section: Discussionmentioning
confidence: 99%
“…This property likely contributes to the important roles of ILCs not only in immune responses against pathogens and sterile inflammation but also in maintaining tissue hemostasis. Nonetheless, differential development and activation of ILCs in a context-and/or disease-specific manner may contribute to inflammatory responses and/or outcome of treatment modalities [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Similarly, kidney possesses NKT cells, MAIT cells, and γδ T cells. [ 20 ] CNS consists of macrophages‐like cells known as microglia along with monocytes, dendritic cells, natural killer (NK) cells, T cells, and B cells. [ 21 ] Similarly, immune cells residing in the adipose tissue include eosinophils, anti‐inflammatory M2 macrophages, and type 2 innate lymphoid cells.…”
Section: Introductionmentioning
confidence: 99%